Connecting micro- and macroscopic variables in the design of a granular stirrer using simulations - Arévalo, Roberto (Frontiers in Soft Matter, 2023)
Predicting the mixing or segregation of granular of dense materials is difficult due to their athermal nature and lack of general theories. The goal of this research is to improve the design (diameter of the cylinder) and operation (rotational frequency of the screw conveyor) of the stirrer to attain good mixing. We characterize the mixing by some macroscopic measures and relate its behavior with the design parameters. Afterward, we compute some microscopic measurements that characterize the movement of the spheres and relate them with the operating conditions. The quality of mixing is found to depend on the rotation frequency of the screw conveyor and the gap between the latter and the enclosing cylinder. Besides, some relationships between micro- and macroscopic measures are drawn. This approach can provide guidance on the design or operation of devices to handle granular media when their microscopic behavior is previously known.